2021
DOI: 10.1080/0376835x.2021.1880373
|View full text |Cite
|
Sign up to set email alerts
|

Progressivity of out-of-pocket payments and its determinants decomposed over time

Abstract: This study estimates progressivity of out-of-pocket (OOP) health payments and their determinants using South African Income and Expenditure Surveys. Concentration is decomposed to examine the effect of household determinants on OOP inequality, shedding light on how progressivity/regressivity is related to changes in the concentration and elasticities of the determinants over time. Our results suggest that actual OOP health expenditures are concentrated among non-poor households, although less so now than in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…The exploratory variables (covariates) are informed by Andersen’s Health Behaviour model, distinguishing the following three categories of factors affecting access to healthcare services [ 22 ]: (i) enabling factors , including gender, age group, and marital status; (ii) predisposing factors , including educational level, economic status, employment status, and health insurance coverage status; and (ii) need factors , including periodic check-ups and self-rated health. In addition, these socioeconomic factors are based on evidence from previous studies that demonstrated their relative influence on OOP health expenditure [ 23 25 ].…”
Section: Methodsmentioning
confidence: 99%
“…The exploratory variables (covariates) are informed by Andersen’s Health Behaviour model, distinguishing the following three categories of factors affecting access to healthcare services [ 22 ]: (i) enabling factors , including gender, age group, and marital status; (ii) predisposing factors , including educational level, economic status, employment status, and health insurance coverage status; and (ii) need factors , including periodic check-ups and self-rated health. In addition, these socioeconomic factors are based on evidence from previous studies that demonstrated their relative influence on OOP health expenditure [ 23 25 ].…”
Section: Methodsmentioning
confidence: 99%
“…Equivalence scales also underpin means‐tests for government transfers, tax policy—especially exemptions for dependents—and subsidy policy, such as those that might focus on support for young children. Equivalence scales are also used in the estimation of catastrophic health expenditures (Ataguba, 2012; Koch & Setshegetso, 2020, 2021), although Koch (2018) suggests that the choice of scale does not make much difference in the underlying estimation of catastrophe, when following the World Health Organization method (Xu, 2005). Ye and Koch (2021) and Ye et al (2019) adopt the concept to determine household energy requirements and measure energy poverty.…”
Section: Introductionmentioning
confidence: 99%